2022
DOI: 10.1007/s11356-022-25048-4
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in the stability of biodiesel fuels: recent progress and challenges

Abstract: Fewer fossil fuel deposits, price volatility, and environmental concerns have intensified biofuel-based studies. Saccharification, gasification, and pyrolysis are some of the potential methods of producing carbohydrate-based fuels, while lipid extraction is the preferred method of producing biodiesel and green diesel. Over the years, multiple studies have attempted to identify an ideal catalyst as well as optimize the abovementioned methods to produce higher yields at a lower cost. Therefore, this present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 146 publications
0
3
0
Order By: Relevance
“…A large part of these antioxidants can be decomposed or destroyed during transesterification or refining processes [101,102]. Considering this aspect, biodiesels obtained from unrefined vegetable oils have a higher amount of natural antioxidants in their composition and, consequently, a greater stability to degradation by oxidation, but do not meet other conditions necessary to be used as fuel [103]. Phenolic compounds extracted from plants, such as tocopherols, lycopene, carotenoids, astaxanthin, canthaxanthin, zeaxanthin, caffeic acid, gallic acid, ferulic acid, vanillin, sinapic acid, p-coumaric acid, cinnamic acid, eugenol, sesamol, vanillic acid, resveratrol, etc., have antioxidant properties, and are currently widely produced and marketed.…”
Section: Natural Antioxidantsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large part of these antioxidants can be decomposed or destroyed during transesterification or refining processes [101,102]. Considering this aspect, biodiesels obtained from unrefined vegetable oils have a higher amount of natural antioxidants in their composition and, consequently, a greater stability to degradation by oxidation, but do not meet other conditions necessary to be used as fuel [103]. Phenolic compounds extracted from plants, such as tocopherols, lycopene, carotenoids, astaxanthin, canthaxanthin, zeaxanthin, caffeic acid, gallic acid, ferulic acid, vanillin, sinapic acid, p-coumaric acid, cinnamic acid, eugenol, sesamol, vanillic acid, resveratrol, etc., have antioxidant properties, and are currently widely produced and marketed.…”
Section: Natural Antioxidantsmentioning
confidence: 99%
“…It was found that tocopherols show antioxidant activity only if their concentration is approximately equal to their concentration in vegetable oil, and at a higher concentration, they could act as an oxidant agent [27,105]. Further, in many studies, it has been shown that tocopherols, compared to synthetic antioxidants, have a limited antioxidant effect on biodiesel fuels, being more effective for diesel than for biodiesel produced from vegetable oils or their esters [101][102][103]. In addition, tocopherols are compounds that oxidize easily in air, and they are only stable in an inert environment (in the absence of air).…”
Section: Natural Antioxidantsmentioning
confidence: 99%
“…The origin of FAME can be edible feedstock (1st generation), nonedible feedstock (2nd generation), algae feedstock (3rd generation), or microbial feedstock (4th generation). The FAME feedstock used is dependent on the geographical region and mainly comprises first-generation crop oils derived from palm, rapeseed/canola, soybean, corn, and sunflower; used cooking oils (UCO); and animal fats. , The primary feedstocks in Europe are rapeseed and palm oil, UCO, and minor amounts of soybean oil, sunflower oil, and animal fats . In the US, mostly soybean, corn, and canola oils are used, as well as recycled feedstocks .…”
Section: Introductionmentioning
confidence: 99%